DAMPAK TURBULENSI LINGKUNGAN, SELF-ESTEEM DAN BUDGET EMPHASIS TERHADAP BUDGETARY SLACK - Parmin Ishak; Nur Lazimatul Hilma Sholehah (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2023)
The study aims for: (1) to know how much environmental turbulence, self-esteem and budget emphasis simultaneous affect the slack budgetary; (2) know how much environmental turbulence affects the slack budgetary; (3) know how much self-esteem affects the slack budgetary; (4) knows how much the budget emphasis affects the slack budgetary. This kind of research is quantitative research. The object of this research is boelamo district BKAD. The sample sampling technique in this study is using the tedium sampling method. Data collection was conducted via a survey method using a questionnaire that was directly distributed to all employees in boalemo county records. The study suggests that (1) environmental turbulence, self-esteeme and budget emphasis significantly simultaneously affect the slack budgetary, (2) environment turbulence does not significantly to the slack budgetary, (3) self-esteem has a positive and significant impact on the slack budgetary, (4) budget emphasis have an insignificant positive effect on the slack budgetary.